Case report: Autoimmune hemolytic anemia caused by warm and cold autoantibodies with complement activation—etiological and therapeutic issues - Turudic, Daniel; Dejanovic Bekic, Sara; Mucavac, Lucija; Pavlovic, Maja; Milosevic, Danko; Bilic, Ernest (Frontiers in Pediatrics, 2023)
Introduction Research on mixed warm and cold autoantibodies in autoimmune hemolytic anemia (AIHA) targeting erythrocytes [red blood cells (RBCs)] and platelets is scarcely reported. Case presentation In this study, we present the case of a 5-year-old boy with positive direct [anti-IgG (1+), anti-IgG-C3d (3+)], and indirect antiglobulin (Coombs) tests. The RBCs were coated with polyspecific-positive, warm IgG autoantibodies alongside activated complement components. Plasma-containing immunoglobulin M (IgM) class autoantibodies were found in 1:64 titers with a wide temperature range of 4°C–37°C. The platelets were also coated with IgM autoantibodies. There was a reduction in the levels of the classical and alternative complement pathways, such as C3, C4, ADAMTS13 metalloprotease activity, factor H antigen, complement factor B antigen, and C1q antigen alongside the elevated sC5b-9 terminal complement complex. Hematuria and/or proteinuria, reduced diuresis, and elevated levels of serum creatinine were absent. The kidney ultrasound report was normal. A recent combination of Epstein–Barr virus (EBV) and cytomegalovirus (CMV) infection was found. The first-line treatment consisted of intravenous methylprednisolone [4 mg/kg/body weight for the first 72 h (q12 h), followed by 2 mg/kg body weight for 21 consecutive days with a slow steroid reduction until plasmapheresis (PLEX)]. After the patient showed limited response to corticosteroid therapy, rituximab (375 mg/m2) was administered once a week (five doses in total), with vitamins B9 and B12. These strategies also showed limited (partial) therapeutic benefits. Therefore, the treatment was switched to PLEX (five cycles in total) and intravenous immunoglobulin (IVIg) (1 g/kg/5 days). This combination significantly improved RBC count and platelet levels, and C3 and C4 levels returned to normal. A follow-up of 2.5 years after treatment showed no sign of relapse. A genetic analysis revealed a rare heterozygous intronic variation (c.600-14C > T) and heterozygous Y402H polymorphism of the CFH gene. c.600-14C > T mutation was located near the 5′ end of exon 6 in the gene encoding the complement C3 protein of unknown significance. We presumed that the complement regulators in our patient were sufficient to control complement activation and that complement blockade should be reserved only for devastating, life-threatening complement-related multiorgan failure. Conclusion We believe that EBV and CMV triggered AIHA, thus activating the complement cascade. Hence, we used corticosteroids, rituximab, vitamins B9 + B12, PLEX, and fresh frozen plasma (FFP) as treatment. Final remission was achieved with PLEX and FFP. However, an additional late effect of B12 rituximab and the disappearance of long-lived circulating plasma cells should not be completely ignored. Complement activation with a genetic background should be assessed in severe warm and cold hemolytic anemias caused by autoantibodies.